Anesthetic and Obstetric Outcomes in Morbidly Obese Parturients: A 20-Year Follow-up Retrospective Cohort Study. Issue 4 (December 2015) - Tonidandel, A.; Booth, J.; D'Angelo, R.; Harris, L.; Tonidandel, S.
Abstract : ( Int J Obstet Anesth . 2014;23(4):357–364)